The study of fractional composition of pectin substances in vegetables and technical means of its obtaining - Belousova Anna I.; Donchenko Lyudmila V. (E3S Web of Conferences, 2020)
The article discusses the feasibility of automation of technological process of liquid pectin obtaining for the production of functional beverages to ensure a given quality and required physiological properties. There were presented the comparative differences between traditional operator consoles and workstations. There was justified the expediency of control and regulation of main technological parameters of the process of pectin extraction. There was described the algorithm of evaluating the results of real-time monitoring of the process.